A Study of Some Biochemical Variables and Functional Indicators and Their Relationship to the Achievement of 200m Young Runners - Sabeeh Hussein, Eman (International Journal of Psychosocial Rehabilitation, 2020)
Biomechanics is considered one of the sciences that have contributed to the scientific progress of the motor performance of man in general and sports in particular, and the main content of this science in the field of physical education is the study of the causes of movement and knowledge of the relationship of scientific movement with all the physical, functional, and psychological variables associated with movement in order to reach the most appropriate and better solution. Anthletex events are events that differ from each other in terms of characteristics and components; they include short, medium, and long-distance running activities in addition to jumping and throwing activities, and because the biomechanical variables and functional indicators are considered one of the important factors related to sports excellence because of their association with the skill aspects that require each sports activity in general, and the competition ran the 200m Bos FH question in particular, so it is recognized as one of the important pillars to guide studies and a major and influential role in the development of the event. Run 200 m, and the research aims to: 1. Determine some biochemical variants of young 200-meter runners. 2. Determining some job indicators for the 200 million youth contestants. 3. Finding a correlation relationship between some biochemical variables and the achievement of hostile runs of 200 meters for a youth. 4. Finding a correlation between some job indicators and achieving a hostile runner who ran 200 meters. A descriptive approach was used for young runners running 200 meters from (8) runners, (20) biochemical variables, and (7) functional indicators. After the data has been processed, interpreted, and discussed, the following conclusions are reached: 1. There was a significant correlation between the variable number of steps and the four stages with the completion of the 200-meter race for young runners. 2. There was a significant correlation between the variable of step length and all four stages of achieving 200m running for young runners. 3. There was a significant correlation between the step frequency variable and all its four stages with the completion of the 200-meter race for the young runners. 4. The presence of a significant correlation between the time variable every 50m and all its four stages with achieving 200m running for young runners. 5. There is a significant correlation between the medium speed variable and its four stages, with the completion of the 200-meter race for the young runners. 6- Significant correlations were found between all functional indicators (pulse at rest, systolic blood pressure at rest, diastolic blood pressure at rest, anaerobic stride, Harvard stride, vertical dip (workout), and Parach energy index) with a score of 200 meters. It works for young runners.